The Diagnostic Accuracy of Ultrasound in Assessment of Myometrial Invasion in Endometrial Cancer: Subjective Assessment versus Objective Techniques - Frühauf, Filip; Zikan, Michal; Semeradova, Ivana; Dundr, Pavel; Nemejcova, Kristyna; Dusek, Ladislav; Cibula, David; Fischerova, Daniela (BioMed research international, 2017)
The aim of this study was to assess the diagnostic accuracy of subjective ultrasound evaluation of myometrial invasion of endometrial cancer and to compare its accuracy to objective methods. All consecutive patients with histologically proven endometrial cancer, who underwent ultrasound evaluation followed by surgical staging between January 2009 and December 2011, were prospectively enrolled. Myometrial invasion was evaluated by subjective assessment using ultrasound (<50% or ≥50%) and calculated as deepest invasion/normal myometrium ratio (Gordon's ratio) and as tumor/uterine anteroposterior diameter ratio (Karlsson's ratio). Histological assessment from hysterectomy was considered the gold standard. Altogether 210 patients were prospectively included. Subjective assessment and two objective ratios were found to be statistically significant predictors of the myometrial invasion (AUC = 0.65, p value < 0.001). Subjective assessment was confirmed as the most reliable method to assess myometrial invasion (79.3% sensitivity, 73.2% specificity, and 75.7% overall accuracy). Deepest invasion/normal myometrium (Gordon's) ratio (cut-off 0.5) reached 69.6% sensitivity, 65.9% specificity, and 67.3% overall accuracy. Tumor/uterine anteroposterior diameter (Karlsson's) ratio with the same cut-off reached 56.3% sensitivity, 76.4% specificity, and 68.1% overall accuracy. The subjective ultrasound evaluation of myometrial invasion performed better than objective methods in nearly all measures but showed statistically significantly better outcomes only in case of sensitivity.
Keywords: nádory endometria; lidé středního věku; Endometrial Neoplasms; lidé; senioři nad 80 let; senioři; Female; Neoplasm Invasiveness; myometrium; Aged; Ultrasonography; Middle Aged; ultrasonografie; Myometrium; Aged, 80 and over; invazivní růst nádoru; ženské pohlaví; Humans